The Social Well-Being Status of Female Rice Mill Workers in Bangladesh: An Empirical Study (Global Journal of Human-Social Science, 2024)
Rice mill workers can be considered as the lifeline to maintain the country s food security More than half of them were female However a few studies focused on socioeconomic conditions and well-being of rice mill workers The present study aimed to assess the social well-being of female rice mill workers in Bangladesh and socio-economic factors affecting it The data were collected from a sample of 398 female rice mill workers age mean 31 82 years SD 8 39 years who were selected through mixed sampling method The data were collected using face-to-face interview with a structured questionnaire The questionnaire included questions about personal information education income living environment health violence belongingness equality working environment and social well-being Results showed that there was a lower household income a lower standard of living environment lack of health and recreational facilities unhealthy working environment and a lower social well-being of female rice mill workers Regression analysis showed that education number of rooms for living number of families using bathrooms hygiene of bathrooms leave facilities discrimination in working hours and mill environment were associated with lower social well-being Rice mill owners the government and non-governmental organizations should come forward to enhance the living standards and well-being of these workers
Keywords: social well-being; female workers; rice mill; Bangladesh